Project Atmapratistha : an Inspiring Public Private Partnership in Assam - J.Deka; P.Nath; D.K.Gogoi; Vikram Singh (Journal of Agricultural Extension Management, 2025)
Implications of WTO have provided new dimensions to farmers’ needs, which are changing and diversifying from the age old need for food. Traditional public extension system suffers from many limitations and is not fully capable of keeping pace with the changing scenario. The gaps are expanding day by day and need to be bridged by participation of private sector in the extension process. Therefore, Public-Private Partnership is gaining momentum in agricultural development